Nad Niemnem - Orzeszkowa, Eliza, 1842-1910. (Poznan : Wydawnictwo Podsiedlik-Raniowski i Spolka, 1997)
A novel emphamsizing the differences between the lives of village people and those of the Manor, in late 19th century Poland.